Surge-Heading Guidance-Based Finite-Time Path Following of Underactuated Marine Vehicles - Wang, Ning; Sun, Zhuo; Jiao, Yuhang; Han, Guangjie (IEEE transactions on vehicular technology, 2019)
In this paper, a surge-heading guidance-based finite-time path-following control (SHG-FPC) scheme is created for an underactuated marine vehicle with complex unknowns. In lieu of line-of-sight guidance, both surge and heading can be guided by adapting to path-following errors and this can greatly enhance the decision-making autonomy pertaining to guidance of kinematics and dynamics, simultaneously. Complex unknowns can be exactly identified by virtue of the devised finite-time uncertainty observer (FUO), by which FUO-based nonsmooth control laws are able to achieve accurate guidance tracking, and thereby, contributing to entire finite-time path-following performance with strong robustness. Simulation results demonstrate the remarkable performance of the proposed SHG-FPC scheme.